Change In Classroom Practice - Farrow, Steve (Taylor & Francis, 1994)
Over the last ten years deliberate and determined efforts have been made to improve schooling. This book charts recent and current developments in the practical business of changing classroom practice to make schools more effective. It is devoted to detecting the effects on classroom practice of the efforts made to improve schools and classrooms, and to understanding how classroom practice changes. Contributors include advisory teachers, Higher Education HE tutors and researchers, and work described ranges from early years' classrooms to post-experience course outcomes and the tracking of Inservice education and training INSET effectiveness.